Interpreting power relations and aesthetic stuttering in TikTok’s X&Y vertical video - Yusanto, Freddy; Hidayat, Dasrun; Lyndon, Novel Anak (Jurnal Kajian Komunikasi, 2026)
Background: While previous studies have often celebrated the ergonomic advantages of mobile video, this research identifies a critical tension in the transition of professional cinematic language to vertical formats. Purpose: This study seeks to uncover the power dynamics and aesthetic modifications within professional vertical productions. Methods: Using a qualitative methodology based on John Fiske’s semiotic analysis (levels of reality, representation, and ideology), this study analyzes the professional vertical film X&Y (Chapter One), created by TikTok Indonesia. Results: Through a close reading of cinematographic elements, the findings reveal a phenomenon of “aesthetic stuttering.” At the level of reality, high-resolution technology successfully builds visual intimacy through the micro-details of facial expressions. However, at the level of representation, the film remains trapped in horizontal cinematic conventions, characterized by the dominance of objective camera angles and a lack of subjective Point of View (POV) exploration typical of vertical video culture. Conclusion: Ideologically, this “stuttering” reveals a covert power struggle in which professional creators negotiate between the dictates of platform algorithms and the entrenched hegemony of traditional film standards. Implications: The discovery of “aesthetic stuttering” suggests that professional content creators must shift from a “cropped horizontal mindset” toward developing a new visual language that is inherently participatory and immersive in order to maximize the unique potential of a vertical narrative.